Retrospective analysis of outcomes in patients with acute hypertriglyceridemic pancreatitis treated without therapeutic plasma exchange. Issue 2 (7th December 2020) - Hutchison, Bailey; Collins, Julia; Makar, Robert S.; Dzik, Walter
Abstract: Background: Therapeutic plasma exchange (TPE) is often used to decrease serum triglyceride levels in hypertriglyceridemic pancreatitis (HTGP), although there is a lack of high‐quality data directly attributing improved clinical outcomes to TPE. There are currently no large studies evaluating the treatment of HTGP without TPE. Study Design and Methods: This study retrospectively analyzes clinical and laboratory outcomes of 115 encounters at Massachusetts General Hospital (MGH) wherein a HTGP patient was treated without TPE and compares these outcomes to those of HTGP patients in the literature treated with TPE. Results: After management without TPE, the median reduction in serum triglycerides was 48% (IQR 29%‐63%) on day one and 74% (IQR 60%‐84%) on day two in 115 episodes of acute HTGP. The reductions were comparable to those reported in several large published case series after a course of TPE (65.8% to 81% reduction). In 25 episodes among 24 patients, treatment included admission to an intensive care unit. There was no significant difference in mortality or rates of local complication, mechanical ventilation, or use of vasoactive medication or renal replacement therapy between this ICU subset and published cohorts (all P > .05). Conclusions: HTGP patients who do not receive TPE do not experience inferior outcomes compared to patients in the literature treated with TPE. The added value of TPE in HTGP, if any exists, needs to be demonstrated in controlled trials.